KOMPETISI INTI SEBAGAI FAKTOR YANG MEMPENGARUHI KUALITAS JIWA KEWIRAUSAHAAN PEKERJA INFORMAL PEREMPUAN DALAM PEROLEHAN NILAI TAMBAH USAHA - Dian Retnaningdiah (Program Studi Manajemen, 2017)
This study is want to know the effect of creativity and innovation as of the female informal sector worker’s quality. The survey methode has been in this research. The sample number used is 35 respondents from the small medium entrepreneurs with the purposive random sampling technique. The data analysis used reliability and validity for measuring the questionares. The regresion analysis is used as well. By using 5% level of significant, the result show that in partially and simultaneously both creativity both creativity and innovation are the factors affecting the female informal sector workee’s quality.